(untitled) (Darya Ganj, New Delhi, 2001)
Contents of material: 1/ Introduction. 2/ Modern library systems. 3/ Modern library functions. 4/ Nature of planning. 5/ Modern library automation. 6/ Impact of computers. 7/ Networking systems
Keywords: Library science,Modern library systems